In Vitro α-Amylase Inhibition and Antioxidant potential of Chloroform Fraction of Hydroalcoholic Extract Obtained from Hyptis Suaveolens - P. Nayak, D.M. Kar, S. Nayak (Journal of Applied Pharmaceutical Science, 2014)
The plant Hyptis is an effective medicinal herb and a well known medicinal plant in herbal world. The present study was aimed to investigate the α-amylase inhibition and antioxidant activities of chloroform fraction of H. suaveolens. Chloroform fraction of H. suaveolens was screened for α-amylase inhibition activity by 3, 5-dinitrosalicylic acid (DNSA) method respectively. and antioxidant activity was evaluated by 1,1-diphenyl-2-picryl-hydrazile (DPPH) free radical scavenging, Super oxide radical Scavenging, nitric oxide (NO) radical scavenging, and 2.2’-azinobis-3-ethylbenzothiazole-6-sulfonic acid (ABTS) radical scavenging assays. The chloroform fraction of H. suaveolens showed effective α-amylase inhibition activity (IC50 57.34µg/ml). Chloroform fraction demonstrated significant antioxidant activity in all the in vitro antioxidant models. Moreover, the chloroform fraction was found to be extremely effective in scavenging DPPH (IC50 57.51 µg/ml) while compared to super oxide (IC50 61.36 µg/ml), NO (IC5076.3 µg/ml) and ABTS radical (IC50 93.16 µg/ml) scavenging activity. In conclusion, from the results of present study it is established that antioxidant and alpha-amylase inhibitory activity of chloroform fraction of H. suaveolens may contribute in its earlier observed antidiabetic potential.
Keywords: Alpha-amylase inhibitory activity, H. suaveolens, DPPH, Super oxide radical Scavenging activity.